2013
DOI: 10.1038/aps.2013.48
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin promotes angiogenesis during the early embryonic development of zebrafish

Abstract: Aim: To investigate the embryotoxicity of dihydroartemisinin (DHA), the main active metabolite of artemisinin, in zebrafish, and explore the corresponding mechanisms. Methods: The embryos of wild type and TG (flk1:GFP) transgenic zebrafish were exposed to DHA. Developmental phenotypes of the embryos were observed. Development of blood vessels was directly observed in living embryos of TG (flk1:GFP) transgenic zebrafish under fluorescence microscope. The expression of angiogenesis marker genes vegfa, flk1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…However, it seems that ART derivatives can arouse potential embryotoxicity in experimental animals. For example, dihydroartemisinin can bring about abnormal embryonic phenotypes and promote early embryonic angiogenesis in zebrafish [72]. Preclinical studies have demonstrated that artesunate can induce congenital malformations in rodents [73,74].…”
Section: Foregoing Researches On the Anticancer Effect Of Artemisimentioning
confidence: 99%
“…However, it seems that ART derivatives can arouse potential embryotoxicity in experimental animals. For example, dihydroartemisinin can bring about abnormal embryonic phenotypes and promote early embryonic angiogenesis in zebrafish [72]. Preclinical studies have demonstrated that artesunate can induce congenital malformations in rodents [73,74].…”
Section: Foregoing Researches On the Anticancer Effect Of Artemisimentioning
confidence: 99%
“…Similar results have been observed in ovarian cancer cells in vitro and in vivo [95] . This group has also demonstrated the potential embryotoxicity of dihydroartemisinin in the embryos of wild-type and TG (flk1: GFP) transgenic zebrafish [96] .…”
Section: Introductionmentioning
confidence: 99%
“…The zebrafish model was also used to test the potential embryotoxicity of DHA [ 52 ]. DHA exposure (1–10 µg/mL) during primitive hematopoiesis and hematopoietic stem cell specification caused an abnormal embryonic phenotype (pericardial edema, abnormal trunk axis, abnormal pigmentation), developmental delays or death, similarly to the other animal models.…”
Section: Developmental Toxicity Data Of Artemisinin Derivativesmentioning
confidence: 99%